Assessment of a novel system utilizing gases exhausted from a ship's engine for power, cooling, and desalinated water generation. (5th February 2021) - Cao, Yan; Mihardjo, Leonardus W.W.; Dahari, Mahidzal; Mustafa Mohamed, Abdeliazim; Ghaebi, Hadi; Parikhani, Towhid
Highlights: A trigeneration system based on exhausted gases from a ship's engine is simulated. The system's products are power, cooling, and desalinated water. Completely energetic and exergetic study for performance analysis is performed. Energy and exergy efficiencies of the system are 60.4%, 39.7%, respectively. In 22% of ammonia concentration, desalinated water production rate is optimized to 1.34 kg/s. Abstract: In this paper, an auxiliary trigeneration system driven by gases exhausted from a ship's engine is analyzed from thermodynamic standpoint. The system generates power, cooling, and desalinated water embracing a Kalina cycle in integration with an ejector refrigeration cycle and a humidification dehumidification-based desalination. A parametric study is conducted to analyze the influence of variation in some design parameters on the system's performance. The results indicates that both energy and exergy efficiencies enhance as separator pressure, vapor generator terminal temperature difference and condenser temperature decrease, and evaporator temperature increase. Additionally, Ammonia concentration in the Ammonia–water mixture is seen to have opposing effects on efficiencies. The desalinated water production rate reaches a maximum value of 1.34 kg/s when the Ammonia concentration is equal to 22–23%. Moreover, this parameter declines as the separator pressure increases, and remains unchanged when the evaporator temperature varies. As for cooling, it is deduced that augmentations in separator pressure, evaporator temperature, and vapor generator terminal temperature difference contribute to improvements in cooling output. In a regular input situation, energy and exergy efficiencies, net output power, cooling, and desalinated water production rate are found to be 60.4%, 39.7%, 559.8 kW, 604.7 kW, and 1.31 kg/s, respectively.